Regional Policies and Individual Capabilities: Drawing Lessons from two Experimental Programs Fighting Early School Leaving in France - Thierry Berthet; Véronique Simon (Social Work and Society)
This case study focuses on innovative regional policies fighting early school leaving (ESL) in two French regions, Aquitaine and Rhône-Alpes. After a short presentation of the French policy context on the topic of ESL, we present the two regional programs studied and draw a first line of general conclusions and findings on their implementation. In a second part, we assess these programs in terms of capabilities for voice, education and work. The general aim of the regional programs will thereby be confronted to the beneficiaries and teachers' point of views. Finally we will address the question of the non take-up of institutional devices such as the studied programs as a key question to a capability approach of public action.